The Effect of Demonstration Methods on Gross Motor Skills in Children in Group B1 at Pembina Samporoa Public Kindergarten - Selia Devi; Amrullah Amrullah; Hesti Putri Setianingsih (Journal of Educational Sciences, 2026)
Early childhood education plays an important role in developing all aspects of child development, one of which is gross motor skills. This study aims to determine the application and effect of the demonstration method on the gross motor skills of children in group B1 at Pembina Samporoa State Kindergarten. This study uses a quantitative approach with a descriptive research type and a one-group pretest-posttest design. There were 15 children in the study. Data collection techniques were conducted through observation, interviews, and documentation. Data were analyzed using descriptive percentage analysis and inferential analysis through a t-test at a significance level of 5%. The results showed a significant increase in children's gross motor skills after the demonstration method was applied. In terms of physical endurance, the Very Good Development (VGD) category increased from 7% to 67%. In terms of balance, the VGD category increased from 0% to 20% and the Developing as Expected (DAE) category increased to 53%. In terms of physical strength, the VGD category increased from 0% to 20% and the DAE category increased from 33% to 67%. The t-test results showed that the t-count value of 10.142 was greater than the t-table value of 1.761, so H0 was rejected and H1 was accepted. The conclusion of this study shows that the demonstration method has a significant and effective influence on improving children's gross motor skills, particularly in the aspects of endurance, balance, and body strength.